Innovativeness, risk-taking, and proactiveness in startups: A case study and conceptual development - Gabriel Linton (Journal of Global Entrepreneurship Research, 2019)
Entrepreneurial orientation (EO) research has investigated EO from a unidimensional perspective. By taking the more novel approach of the multidimensional view and focusing on the sub-dimensions, a fine-grained view is achieved. Previous research has often mixed process and outcomes in the conceptualizations of the sub-dimensions of EO. This study argues for making a distinction between process and outcome, which can realize a more nuanced understanding of EO. A qualitative approach is used to achieve a richer understanding of EO. The findings highlight that EO and its sub-dimensions of innovativeness, risk-taking, and proactiveness can be meaningfully divided between the attributes of process and outcome. The sub-dimensions and the attributes of process and outcome are also argued to vary independently of each other.
Keywords: 650; Entrepreneurial orientation; Innovativeness; Risk-taking; Proactiveness; Startups